Receptiveness to Flexible Employment at Hungarian SMEs - Ákos Essősy; Tamás Vinkóczi (DETUROPE)
Nowadays, only companies that are adaptable and flexible in their structure and processes can survive. The basis for a motivated company aiming for peak performance is organisational innovation. Hungary is one of the less innovative countries in Europe. Only organisations that can integrate new solutions smoothly into their everyday operations will remain truly competitive. The Government of Hungary, in its Partnership Agreement with the European Union, set out the goals for improving and supporting the adaptability of enterprises, the promotion of flexible and family-friendly workplace practices and services, and the employment of women with young children. The aim of this study is to demonstrate, through a Hungarian example, the receptiveness of Hungarian small and medium-sized enterprises to flexible forms of employment. The effect of flexible employment on economic adaptability and competitiveness through workforce efficiency and retention is examined. Its aim is the raise the awareness of options to increase employment among Hungarian SME managers.